THE EFFECT OF TEACHER WELFARE, WORK MOTIVATION AND COMPETENCY ON THE PERFORMANCE OF SMPN TEACHERS IN TULANG BAWANG DISTRICT - Ahiruddin Ahiruddin; Sodirin Sodirin; Fahrizi Fahrizi; Trisnowati Josiah; Novalia Novalia (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
This study aims to determine the effect of teacher welfare, work motivation and competence on the performance of SMPN teachers throughout Tulang Bawang Regency. The form of this research is quantitative in the form of a survey. The study was conducted during July 2021. The population in this study were all 1110 SMPN teachers in Tulang Bawang Regency. Banjar Baru District was chosen as the research sample, with a total of 82 teachers. Districts become clusters in this study, so there are 15 clusters, the sample in this study is 10% of the population, namely 1 cluster. The data analysis technique used in this research is Multiple Linear Analysis, Coefficient of Determination Test, and F Test. Based on the hypothesis test results, teacher welfare (X1), and work motivation (X2). Competence (X3) significantly contributes and affects teacher performance (Y) either partially or simultaneously.